The Prognostic Value of Lymphovascular Invasion in Patients With Upper Tract Urinary Carcinoma After Surgery: An Updated Systematic Review and Meta-Analysis - Zhang, Lijin; Wu, Bin; Zha, Zhenlei; Zhao, Hu; Yuan, Jun; Feng, Yejun (Frontiers in Oncology, 2020)
Background and Purpose: Although the prognostic value of lymphovascular invasion (LVI) for upper tract urinary carcinoma (UTUC) has been reported, there is lack of consensus regarding the prognostic factor of LVI in UTUC after radical nephroureterectomy (RNU). The aim of present study was to evaluate the contemporary role of LVI using systematic review and meta-analysis. Materials and Methods: Using Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, we performed a systematic search of Web of Science, PubMed, and EMBASE for all reports published up to July 2019. Cumulative analyses of hazard ratios (HRs)/odds ratios (ORs) and their corresponding 95% confidence intervals were conducted to assess the association between LVI and oncological outcomes and clinicopathological features. Results: Our meta-analysis included 31 eligible studies containing 14,653 patients with UTUC (81–1,363 per study). Our results indicated a significant correlation of LVI with worse cancer-specific survival (HR=1.59, p < 0.001), overall survival (HR=1.55, p < 0.001), recurrence-free survival (HR=1.46, p < 0.001), cancer-specific mortality (HR=1.25, p = 0.047), and recurrence (HR=1.23, p = 0.026). LVI was also correlated with advanced tumor stage (III/IV vs. I/II: OR = 7.63, p < 0.001), higher tumor grade (3 vs. 1/2: OR = 5.61, p < 0.001), lymph node metastasis (yes vs. no: OR = 4.95, p < 0.001), carcinoma in situ (yes vs. no: OR = 1.92, p < 0.001) and positive surgical margin (yes vs. no: OR = 4.38, p < 0.001), but not related to gender (male vs. female: OR = 0.98, p = 0.825) and multifocality (multifocal vs. unifocal: OR = 1.09, p = 0.555). The funnel plot test indicated no significant publication bias. Conclusions: This study demonstrated that LVI was associated with aggressive clinicopathological features. LVI may serve as a poor prognostic factor for patients with UTUC after RNU. Keywords: lymphovascular invasion; upper tract urinary carcinoma; radical nephroureterectomy; prognosis; meta-analysis.